Chemokine CCL4 Induces Vascular Endothelial Growth Factor C Expression and Lymphangiogenesis by miR-195-3p in Oral Squamous Cell Carcinoma - Lien, Ming-Yu; Tsai, Hsiao-Chi; Chang, An-Chen; Tsai, Ming-Hsui; Hua, Chun-Hung; Wang, Shih-Wei; Tang, Chih-Hsin (Frontiers in Immunology, 2018)
The inflammatory chemokine (CC motif) ligand 4 (CCL4) plays an important role in the pathogenesis and progression of cancer. In particular, higher serum CCL4 levels in patients with oral squamous cell carcinoma (OSCC) are associated with a more advanced stage of disease. OSCC accounts for approximately 95% of oral cancer in Taiwan and has a poor prognosis, due to aggressive local invasion and metastasis, leading to recurrence. OSCC spreads preferentially through lymphatic vessels and has the propensity to metastasize to the cervical lymph nodes even in the early stage of disease. Vascular endothelial growth factor (VEGF) is an essential regulator of lymphangiogenesis. In particular, VEGF-C is specific to lymphatic vessel development and VEGF-C expression levels have been found to directly correlate with lymph node metastasis in OSCC. However, it is unclear as to whether CCL4 correlates with VEGF-C expression and lymphangiogenesis in OSCC. We found that CCL4 increased VEGF-C expression and promoted lymphangiogenesis in oral cancer cells in vitro and in vivo. MiR-195-3p mimic reversed CCL4-enhanced VEGF-C expression. CCL4 stimulation of oral cancer cells augmented JAK2 and STAT3 phosphorylation. Thus, CCL4 may be a new molecular therapeutic target for inhibition of lymphangiogenesis and metastasis in OSCC.